Analysis of Criteria for MRI Diagnosis of TMJ Disc Displacement and Arthralgia - Jeffry R. Shaefer; Cara Joy Riley; Paul Caruso; David Keith (Hindawi Limited, 2012)
Aims. To improve diagnostic criteria for TMJ disc displacement (DD). Methods. The standard protocol for MRI diagnosis of DD, using a 12 o'clock reference position, was compared to an alternative protocol. The alternative protocol involves the functional relationship between the condyle and articular eminence, using a line perpendicular to the posterior slope of the eminence as a reference for disc position. The disc location was examined using both protocols, and disc diagnoses were compared in their relationship with joint pain. Statistical analyses included P value, sensitivity, specificity, odds ratio, and kappa statistic. Results. 58 MRIs were interpreted. 36 subjects reported arthralgia; 22 did not. Both protocols demonstrated significance (standard P=0.004, alternative P<0.001) for the ability to predict arthralgia. The odds of arthralgia increased in DD patients diagnosed by standard methods 9.71 times and in DD diagnosed by alternative means 37.15 times. The diagnostic sensitivity decreased 30% using the alternative versus the standard protocol (0.6389 versus 0.9444), while specificity increased 60% (0.9545 versus 0.3636). Conclusions. A stronger relationship occurs between DD and arthralgia when using a function-based protocol. The alternative protocol correctly identifies subjects without arthralgia, who by standard methods would be diagnosed with DD, as having nondisplaced discs, providing a more clinically relevant assessment of TMJ disc displacement.